PROBLEMS OF DEVELOPMENT OF THE RUSSIAN GEOGRAPHICAL EDUCATION IN SECONDARY AND HIGHER SCHOOL - N. Novikov, Alexander; S. Novikova, Maria (Gênero & Direito, 2020)
The article’s authors have defined their goal of not just explaining the general architecture of the geographical education, but indicating the principles of its reorganization at the intra-stage and inter-stage levels, when using the world-view formulas. The dialectics serves as a research method. Its laws are working in the form of the world-view formulas and the world-view guidelines. Problems of training the geographical perception start at the inter-thematic level, when a factor of time between the geographical analysis of the sectorial part and the geographical synthesis of the district part is involved. A loss of the synthesis forms in the geography’s school course leads to the fact that the students cease to perceive the “sectorial geography – district geography” opposition, which makes it impossible to realize the interaction between them under the principle “sectorial analysis – regional synthesis”; a rupture of the geographical education’s integrity, and, on the whole, to a loss of the meaning of the geographical dichotomy’s formula. For the efficient convergence of the university educational programs “Principles of personal and social safety” and “Geographical Education”, the geosecuretology conception was developed into the “Principles of personal and social safety and Geography” program.